Implementation of the waterfall method to the car rental information system at UD Bintang Rimba - Maruloh; Siti Nur Khasanah; Sandra Jamu Kuryanti; Agus Junaidi (Jurnal Mantik, 2023)
With the development of information technology, we are required to be able to keep up with technological developments. At this time, there is still a conventional car rental information system. This causes the information that can be obtained by the public about this car rental is still minimal. So it is necessary to have information that can be accessed widely by the public so that people can easily get information about car rentals without having to come directly to the rental place. Apart from that, it provides benefits for car rental owners in the process of recording reports, no longer needing to use a conventional system that must record every transaction. So that there is an information system development for the car rental. The method of developing software using the waterfall model. With the design of this car rental information system, it is hoped that it can help speed up and simplify car rental so that the rental process becomes more effective and efficient and helps the admin in making reports. The web application can also be a means of assisting companies or agencies in improving the performance of car rental vehicles.